Islamisasi Ekonomi Madzhab Mainstream: Tinjauan, Model dan Implikasi - Hakim, Rahmad (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2016)
The rapid development of Islamic financial institutions lately is quite encouraging, it would be legitimacy that Islam is able to renpond the challenges of globalization and modernization. On the other hand, these developments would make the Islamic financial institutions as a measure of doctrine and Islamic values realized in the lives of all Muslims. But, about Islamic products and a contract that???s practiced is being debated by economist Muslims worldwide.Assuming that ijtihad can be done in mu???amalat according to the rule ???al-Aslu fi l mu???amalāt al ibahah illa ya???ti dalilun ???ala ta??rīmiha??? make this debate more interenting with many opinions expressed by economist Muslims, especially Muslim mainstream economists.The core of the debate between Muslim economists is the method that being used in building the Islamic economic, either by adopting the practices, systems and the values of conventional economics that are relevant to shariah, or through methodology of ushūl fiqh and fiqh which is purely a method derives from treasury of Islamic knowledge constructed by scientist Islam as Imam as-Syāfi???ī, Imam al-Ghāzalī, Izzudīn Ibn Salām, and Imam as-Syātibī.The focus of this paper is, first, examine approaching of some Muslim economists mainstream madzhab in the economics Islamisation. Second, examines the implications of the approach used by the Muslim economists in Islamic economic intitutions (shariah banking/Islamic banking).